2011
DOI: 10.1007/s10140-011-0997-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of acute right lower quadrant abdominal pain: differential diagnoses beyond appendicitis

Abstract: Evaluation of acute right lower quadrant pain remains a common and challenging clinical scenario for emergency medicine physicians due to frequent nonspecific signs, symptoms, and physical examination findings. Therefore, imaging has evolved to play a pivotal role in the emergency setting. While appendicitis is a common cause for acute pain, there are numerous other important differential considerations with which the radiologist must be aware. The purpose of this review is to list an anatomy-based, encompassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
10
0
2
Order By: Relevance
“…However, there is as yet no consensus whether WBC and/or CRP can support the clinical diagnosis of appendicitis . Therefore, imaging has evolved to play a pivotal role in the diagnosis of AA . Our study reported a significant difference in plasma CP and SAA‐1 levels between patients with AA and other abdominal complaints (and a healthy control group).…”
Section: Discussionmentioning
confidence: 62%
“…However, there is as yet no consensus whether WBC and/or CRP can support the clinical diagnosis of appendicitis . Therefore, imaging has evolved to play a pivotal role in the diagnosis of AA . Our study reported a significant difference in plasma CP and SAA‐1 levels between patients with AA and other abdominal complaints (and a healthy control group).…”
Section: Discussionmentioning
confidence: 62%
“…Computed tomography is the imaging modality of choice, by which one can recognize any of the four abovementioned patterns of appendicular diverticular disease. The recommended protocol in patients with right lower quadrant pain comprises contrast-enhanced multi-detector CT of the abdomen obtained in the portal venous phase with or without rectal contrast [1]. In English literature, only very few case reports, where a definite preoperative diagnosis of appendiceal diverticulitis, were made [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The most common pathology in patients with right lower quadrant pain is appendicitis [1]. Although uncommon, appendiceal diverticula are encountered in up to 2 % of appendectomy specimens [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, other inflammatory (appendiceal diverticulitis, inflammatory bowel disease) and non-inflammatory (eg, neoplasia) conditions can also affect the appendix 1. Differentiating infection from other conditions that might affect the appendix can sometimes be difficult radiologically,2 leading to a diagnostic challenge.…”
Section: Introductionmentioning
confidence: 99%